Artefatos para o ensino e aprendizagem das cônicas em sala de aula - Marli Solera (2021)
SOLERA, MARLI. Artifacts for Teaching and Learning Conics in the Classroom. 2021. 88p. Dissertation (PROFESSIONAL MASTER'S DEGREE) – Federal University of Mato Grosso do Sul, Três Lagoas campus, Mato Grosso do Sul, 2021. This paper suggests a conic sections study: ellipse, hyperbola and parabola, through cuts in the cone and using algebraic calculations studied in high school such as matrix multiplication, trigonometry and linear system. It also presents constructions with artifacts to establish a geometric and algebraic relationship focusing on Euclidean geometry. The end of this work highlights an application of this content in a last year of high school using the five hierarchical levels of knowledge according to Van Hiele. Keywords: Conics. Ellipse. Hyperbole. Parabola